The role of ideological and emotional proximity in creating unity in self-organization : A complexity perspective on the self-organization of an online investor community - Alkkiomäki, Outi (My University, 2022)
This study focuses on self-organization, studying an online community, the WallStreetBets, which self-organized in January 2021 and managed to short squeeze the stock of a video-game retailer GameStop. The study focuses on two aspects of self-organization, which are not very well-known: the motives and their connection to organizational involvement. Our current, non-congruent understanding of the motives of self-organization relies heavily on the research on collective action. Further, while self-organization and social capital have been shown to have a connection and organizational involvement is known to influence the creation of social capital, current research does not seem to consider self-organization in relation to organizational involvement. Therefore, there exists a gap in research in terms of the reasons why individuals choose to self-organize and the aspects which might influence those decisions. The data of this study consists of observations, online discussions and interviews and was collected relying on extended case online ethnography methodology. Four members of the community were interviewed, the events discussed in online messages with 103 members of the community and 214 observations were made on the online channel. The data was analyzed using reflexive thematic analysis. Through the process of coding, compound codes were created and subsequently larger themes formed. This research finds that the motives of self-organization could be categorized into essentially four categories: communal motives, oppositional motives, individual motives and financial motives. The motives seemed to be linked to organizational involvement with the community, as those that stated that they participated in the short squeeze for an individual motive, seemed to express a relative lack of proximity to the community. Those that expressed a communal motive, expressed emotional as well as ideological proximity and those that stated oppositional reasons, expressed mostly ideological proximity to the community. Financial motives seemed to be connected to emotional proximity, but the finding was inconclusive in terms of the interview data. Yet, especially the presence of both ideological and emotional proximity seemed to be linked to a higher level of organizational involvement and a greater influence of the community on the individual. Additional research is required in order to gain a more complete understanding of the motives of self-organization as well as the types of aspects, which influence its creation. The phenomenon is still under-researched, and regrettably little is known of its causes. Further attention could to be paid especially to the connection between the individual and the community.
Keywords: self-organization, complexity, organizational involvement, an online investor community